Job Selection and Wages over the Business Cycle - Hagedorn, Marcus; Manovskii, Iourii (American Economic Review, 2013)
We consider a model with on-the-job search where current wages depend only on current aggregate labor market conditions and idiosyncratic match-specific productivities. We show theoretically that the model replicates the findings in Bils (1985) and Beaudry and DiNardo (1991) on the history dependence in wages. We develop a method to measure match qualities in the data and show empirically that various variables summarizing past aggregate labor market conditions have explanatory power for current wages only because they are correlated with match qualities. They lose any predictive power once match qualities are accounted for. (JEL E3, E24, J3)